(untitled) (American Journal of Islam and Society, 2019)
The 2016 Orlando nightclub shooting at a gay dance club in Florida fomented a surge in Islamophobia, as pundits blamed the perpetrator’s Muslim identity for his hateful act. In the aftermath of the violence, vigils across the United States offered forums for Muslim American and other groups to publically express their shared grief and to address homophobia and Islamophobia together. The people affected most intensely by the tragedy were LGBTQ Muslims, who were simultaneously subjected to both intensified homophobia and Islamophobia in the wake of the shooting. This local ethnographic study of Orlando vigils in Michigan examines how the Orlando aftermath encouraged debate about the issue of LGBTQ Muslim visibility and conversation about the potential for Muslim civic leaders and mosque leaders to serve as their allies. During the Orlando vigils, LGBTQ Muslims, allies, and faith leaders drew on, negotiated, and/or resisted various repertoires of mourning and advocacy. Their responses to the Orlando moment provide valuable information about how connections among faith, sexuality, race, and protest are shaping the emergence of LGBTQ Muslim visibilities in the United States today.